Evaluation of Water Losses: Study Case in Intan Banjar Water Supply Company - Setianingsih, Maria; Karnaningroem, Nieke (IPTEK Journal of Proceedings Series, 2019)
Water losses from water distribution networks have become a crucial problem. The BNA (Basic Need Approach) zone has high water losses above the standard for maximum tolerance ministry of public work as 20%. The water losses during September - December 2018 has experienced a fluctuation. the highest losses occurred in October at 36.05%, but in November the level of water losses decreased to 34.17%. The water balance can be used to know to understand the quantity, source, and charge of water losses. The water balance calculation in this study uses the WB-Easy Calc program version 4.05. Based on the result, the percentage of water losses 34,81% with the composition of real losses as 30,61% and apparent losses of 4.21%. On the other hand, the financial impact by the water losses was deficit as Rp. 4.593.648.335. Furthermore, gets to the action for each one of the above main components of the water balance in order to reduce water losses.